Effects of feeding frequency on the productive performance of different tilapia strains. - FRASCÁ-SCORVO, C. M. D. (2011)
This study was conducted during 251 days from April 13th to December 20th in 2010, and it aimed the evaluation of zootechnical performance of three tilapia strains submitted to two feeding frequencies, fed twice a day (2x) and fed once a day (1x).